Calcium decomposition and phantomless bone mineral density measurements using dual-layer-based spectral computed tomography - Mei, Kai; Schwaiger, Benedikt J.; Kopp, Felix K.; Ehn, Sebastian; Gersing, Alexandra S.; Kirschke, Jan S.; Muenzel, Daniela; Fingerle, Alexander A.; Rummeny, Ernst J.; Pfeiffer, Franz; Baum, Thomas; Noel, Peter B. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2018)
Dual-layer spectral computed tomography (CT) provides a novel clinically available concept for material decomposition (calcium hydroxyapatite, HA) and thus to estimate the bone mineral density (BMD) based on non-dedicated clinical examinations. In this study, we assessed whether HA specific BMD measurements with dual-layer spectral CT are accurate in phantoms and vertebral specimens. Dual-layer spectral CT was performed at different tube current settings (500, 250, 125 and 50 mAs) with a tube voltage of 120 kVp. Ex-vivo human vertebrae (n = 13) and a phantom containing different known HA concentrations were placed in a semi-anthropomorphic abdomen phantom. BMD was derived with an in-house developed algorithm from spectral-based virtual monoenergetic images at 50 keV and 200 keV. Values were compared to the HA concentrations of the phantoms and conventional quantitative CT (QCT) measurements using a reference phantom, respectively. Above 125 mAs, which is the radiation exposure level of clinical examinations, errors for phantom measurements based on spectral information were less than 5%, compared to known concentrations. In vertebral specimens, high correlations were found between BMD values assessed with spectral CT and conventional QCT (correlation coefficients > 0.96; p < 0.001 for all). These results suggest a high accuracy of quantitate HA-specific BMD measurements based on dual-layer spectral CT examinations without the need for a reference phantom, thus demonstrating their feasibility in clinical routine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: bone mineral density; computed tomography; material decomposition; osteoporosis; spectral CT